A Corpus of Stories by Members of Civil Society in Rennes, Bretagne, France - Eduardo Chávez Herrera; William Kelleher; Bérénice Briand; Dolly Ramella Georget (Journal of Open Humanities Data)
In this paper, we present the data from ‘Ce qui nous concerne’ (‘What matters to us’), a participative narrative ethnographic research project with civil society organisations in Rennes, France. The data cover a growing corpus of research interviews that are collected with different civil society associations. The data are archived in the Nakala multimodal platform and on an open-access library on the Rennes 2 University WorkAdventure platform. The interviews dataset includes images, .mp3 audio files, transcription text files and rendered versions of the participant stories that make up the interview. The data can be reused for reference, further analysis, and for collaborative initiatives.